Reflective Judgment, Common Sense, and Exemplariness. A Study on the Paradigm of Judgment and its Reception by Alessandro Ferrara and Hannah Arendt (2020)
The paradigm of judgment is a rationality model that intends to stand as a positive alternative in view of the current challenges posed by the linguistic change of philosophy in contemporary thinking. In the face of the difficult task of defending universalist principles in the current culture, this model aims to take a positive stance on issues such as the normative validity that may affect the relationships between human action and deliberation. To fulfill its goal, the paradigm of judgment endorses a form of normativity with no principles (exemplary validity), which is rooted in Kant’s reflective judgment and the sensus communis (common sense) of the humanistic rhetoric tradition. The objective of this paper is to present this model of rationality under the Kantian philosophy, and through an exploration of the historico-philosophical background (Gadamer) and a detour along the humanistic rhetoric tradition (Aristotle and Vico), it seeks to put aside the esthetic emphasis in Kant’s groundwork. Finally, the scope and relevance of this paradigm in the reappropriation by two of its interpreters in contemporary philosophy, Alessandro Ferrara and Hannah Arendt, are assessed.